1998
DOI: 10.3109/10826089809056250
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Based Smoking Cessation Interventions in Adolescents: Description, Feasibility, and Six-Month Follow-Up Findings

Abstract: The impact of adolescent smoking cessation clinics has been disappointing due to low participation rates, high attrition, and low quit rates. This paper describes two computerized self-help adolescent smoking cessation intervention programs: 1) a program utilizing the expert system which is based on the transtheoretical model of change and 2) a popular action-oriented smoking cessation clinic program for teens which was modified for computer presentation. High participation rates in the program among 132 smoke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
47
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(48 citation statements)
references
References 40 publications
1
47
0
Order By: Relevance
“…We found that a web-based, tailored, and theory-based intervention can lead to greater involvement and cognitive processing of asthma information than generic programs, ultimately leading to better outcomes (9,35,36). Making the program school based ensured greater access.…”
Section: Discussionmentioning
confidence: 98%
“…We found that a web-based, tailored, and theory-based intervention can lead to greater involvement and cognitive processing of asthma information than generic programs, ultimately leading to better outcomes (9,35,36). Making the program school based ensured greater access.…”
Section: Discussionmentioning
confidence: 98%
“…218 We examined 13 homogeneous studies of smoking cessation interventions reviewed in that report. [219][220][221][222][223][224][225][226][227][228][229][230][231] Of these studies, 10 [219][220][221][222][223][224][225][226][227][228] reported results in such a way that the results could be extracted and compared. The interventions used in these studies varied, but most considered the stages of smoking cessation pre-contemplation, contemplation and action.…”
Section: Stages Of Change Analysismentioning
confidence: 99%
“…14 Although there is still a dearth of evidence in the results of internet based health promotion interventions, 15 the Internet is regarded as a potentially useful tool to conduct health research interventions. 16 Researchers are starting to conduct web-based interventions for cigarette smoking prevention and cessation, [17][18][19][20][21] depression and anxiety treatment, [22][23][24]25 and other health related studies such as alcohol use, 26 drug abuse, 27 HIV, 28 nutrition and obesity, 14,29,30 and physical activity. 31,32 From completed or on-going web-based intervention programs, researchers have realized the difficulty of retaining participants in longitudinal web-based research, 33 as well as the challenges in both content development and program implementation.…”
mentioning
confidence: 99%